Cycling Exercise Training Enhances Platelet Mitochondrial Bioenergetics in Patients with Peripheral Arterial Disease: A Randomized Controlled Trial - Lin, Ming-Lu; Fu, Tieh-Cheng; Hsu, Chih-Chin; Huang, Shu-Chun; Lin, Yu-Ting; Wang, Jong-Shyan (Thrombosis and Haemostasis, 2021)
Exercise training influences the risk of vascular thrombosis in patients with peripheral arterial disease (PAD). Mitochondrial functionalities in platelets involve the cellular bioenergetics and thrombogenesis. This study aimed to elucidate the effect of cycling exercise training (CET) on platelet mitochondrial bioenergetics in PAD patients. Forty randomly selected patients with PAD engaged in general rehabilitation (GR) with CET (i.e., cycling exercise at ventilation threshold for 30 minute/day, 3 days/week) (GR + CET, n = 20) or to a control group that only received GR course (n = 20) for 12 weeks. Systemic aerobic capacity and platelet mitochondrial bioenergetics that included oxidative phosphorylation (OXPHOS) and electron transport system (ETS) were measured using automatic gas analysis and high-resolution respirometry, respectively. The experimental results demonstrated that GR + CET for 12 weeks significantly (1) elevated VO2peak and lowered VE-VCO2 slope, (2) raised resting ankle-brachial index and enhanced cardiac output response to exercise, (3) increased the distance in 6-minute walk test and raised the Short Form-36 physical/mental component scores, and (4) enhanced capacities of mitochondrial OXPHOS and ETS in platelets by activating FADH2 (complex II)-dependent pathway. Moreover, changes in VO2peak levels were positively associated with changes in platelet OXPHOS and ETS capacities. However, no significant changes in systemic aerobic capacity, platelet mitochondrial bioenergetics, and health-related quality of life (HRQoL) occurred following GR alone. Hence, we conclude that CET effectively increases the capacities of platelet mitochondrial bioenergetics by enhancing complex II activity in patients with PAD. Moreover, the exercise regimen also enhanced functional exercise capacity, consequently improving HRQoL in PAD patients.
Keywords: peripheral arterial disease; exercise; platelet; mitochondria